Molecular structures, chemical properties and biological activities of polysaccharide from Smilax glabra rhizome - Je Young Lee (2018)
© 2018 The water-soluble crude polysaccharides, extracted from the rhizome of Smilax glabra, were fractionated using an anion exchange chromatography, yielding two fractions, F1 and F2. The crude and fractions (F1 and F2) mainly consisted of carbohydrates (66.7%–91.1%), proteins (7.30%–23.9%) and minor amount of sulfates (1.60%–9.40%). Glucose was the major monosaccharide unit of the polysaccharides with different levels of sugar constituents including galactose, arabinose, rhamnose and mannose. The molecular weight (Mw) of crude and fractions ranged from 32,102–6.3 × 103 g/mol. The crude and fractions could stimulate RAW264.7 cells to release nitric oxide and cytokines via up-regulation of their mRNA expression by the activation of NF-κB and MAPKs pathways. The related pattern recognition receptors (PRRs) on the surface of the cells appeared to be TLR2 and CR3. The GC–MS analysis revealed that the main backbone of the most immune-enhancing F2 was (1 → 4)-linked glucose and galactose chain with minor linkages of (1 → 6)-galactose, (1 → 3)-mannose, (1 → 2)-rhamnose and (1 → 5)-arabinose with some branches at C-3 and C-4 rhamnose, or C-6 galactose.